STATUS PENYELENGGARAAN PERADILAN HAM DI INDONESIA BERBASIS HUKUM INTERNASIONAL - Nurul Huda (Faculty of Law, Universitas Diponegoro, 2015)
The era of respect for Human Rights (HAM) in Indonesia was marked by the issuance of regulatory/legal instruments both in the state constitutional amendment after amendment and legislation in the form of legislation include Act No. 26 of 2000 on Human Rights Court which is substantially oriented the Rome Statute. Apparently, Act No. 26 of 2000 is a product of the criminal policy